PENGHAPUSAN LEMBAGA PRAPERADILAN DALAM RUU KUHAP 2012 - Simarmata , Berlian (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2022)
The data used in this study is secondary data, in the form of primary legal materials, secondary legal materials and tertiary legal materials. The analysis was carried out in a juridical qualitative manner, and conclusions were drawn inductively. This study aims to determine the rationale for abolishing pretrial institutions in the 2012 KUHAP Bill and the consequences of the abolition of pretrial institutions in the 2012 KUHAP Bill towards respecting the human rights of suspects/defendant in Indonesia. The results showed that the rationale for abolishing pretrial institutions in the 2012 Criminal Procedure Code Bill was that in the 2012 Criminal Procedure Code Bill, the police and prosecutors were no longer given the authority to make arrests to the detention, so it was no longer possible to make wrongful arrests to the detention. The results showed that the rationale for abolishing pretrial institutions in the 2012 Criminal Procedure Code Bill was that in the 2012 Criminal Procedure Code Bill, the police and prosecutors were no longer given the authority to make arrests to the detention, so it was no longer possible to make wrongful arrests to the detention.